 3. SINGULARITIES FUNCOIDS: SPECIAL CASES PROOF ATTEMPTS

44

K

(

z

S

Ob

ν

K

up

z

x

S

I

:

x

v

K

∧ ∃

z

S

Ob

ν

K

up

z

y

S

Y

:

y

v

K

)

(

z

S

Ob

ν

K

up

z

x

S

J

:

x

v

K

∧ ∃

z

S

Ob

ν

K

up

z

y

S

Y

:

y

v

K

)

(

z

S

Ob

ν

: (

K

up

z

x

S

I

:

x

v

K

∧ ∀

K

up

z

y

S

Y

:

y

v

K

))

(

z

S

Ob

ν

: (

K

up

z

x

S

J

:

x

v

K

∧ ∀

K

up

z

y

S

Y

:

y

v

K

))

(

z

S

Ob

ν

: (

K

up

z

: (

x

S

I

:

x

v

K

∧ ∃

y

S

Y

:

y

v

K

)))

z

S

Ob

ν

K

up

z

: (

x

S

J

:

x

v

K

∧ ∃

y

S

Y

:

y

v

K

)

I

[SLA(

ν

)]

Y

J

[SLA(

ν

)]

Y

.

To finish the proof we need to fulfill ?? in the above formula. For this it’s

enough to prove

K

up

z

x

S

I

S

J

:

x

v

K

K

up

z

x

S

I

:

x

v

K

∨ ∀

K

up

z

x

S

J

:

x

v

K

.

If

z

=

Z

is a principal funcoid, then

K

up

z

x

S

I

S

J

:

x

v

K

x

S

I

S

J

:

x

v

z

x

S

I

:

x

v

z

∨ ∃

x

S

J

:

x

v

z

K

up

z

x

S

I

:

x

v

K

∨ ∀

K

up

z

x

S

J

:

x

v

K

.

Following

the

idea

of

[[the

proof

in

this

math.stackexchange.com

question|http://math.stackexchange.com/questions/562908/an-implication-
involving-filters#562974]] it is easy to show that our implication is true if
up

z

is closed regarding finite meets. See [[this page|Singularities funcoids: some

special cases]] for attempts to set it true. The question is whether our statement
holds for non-principal funcoids. Or is there a counterexampe?

3. Singularities funcoids: special cases proof attempts

To prove that GR(∆

×

FCD

∆) is closed under finite intersections, it’s enough to

prove that for every

f

GR(∆

×

FCD

∆) there is a positive

ε

such that

x

]

ε

;

ε

[:

f x

∆.

Really, under this assumption:
For

g

GR(∆

×

FCD

∆) exists

ζ >

0 such that

x

]

ζ

;

ζ

[:

gx

∆. Let

η

=

min

{

ε, ζ

}

. So

x

]

η

;

η

[: (

h

f

i

x

∧ h

g

i

x

∆) and so

x

]

η

;

η

[:

h

f

g

i

x

that is

x

]

η

;

η

[:

h↑

FCD

(

f

g

)

i

{

x

} w

∆ and consequently

f

g

GR(∆

×

FCD

∆).